How Does Creativity and Environmental Support Matter on University Students’ Digital Entrepreneurial Intention? : A Mediated Model - Indira, Fransisca Rahcmawati; Wardani, Dewi Kusuma; Murwaningsih, Tri (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to investigate the effects of self-perceived creativity and environmental support on university students' digital entrepreneurial intentions while also examining a mediation model. This research used a survey method with a quantitative approach. The data was collected involving undergraduate students in Economic Education from three universities in Central Java province. The study engaged 531 population and 229 samples selected using the proportionate random sampling method. SEM-PLS analysis was employed for data analysis. The findings suggest that digital entrepreneurial intention is positively, albeit not significantly, impacted by self-perceived creativity. Meanwhile, digital entrepreneurial intention is positively and significantly impacted by both environmental support and digital entrepreneurial self-efficacy. Moreover, digital entrepreneurial self-efficacy is also positively and significantly impacted by self-perceived creativity and environmental support. Then, the mediation models are also accepted. The results suggest fostering creativity-based learning programs, training, internships, and short courses to enhance students' confidence in digital entrepreneurship and entrepreneurial intentions. To this end, collaborating with universities, governments, and private sectors is crucial in executing such initiatives.